Exploring the influence of architectural elements of Balai Besar Kedah on the Malay traditional architecture - Abdul Majid, Noor Hanita; Ahmad Kamil, Husna Munirah; Samsudin, Abu Dzar; Ali, Maisarah (Universiti Kebangsaan Malaysia (UKM), 2018)
Balai Besar Kedah is a royal audience hall built within the complex of Kota Setar Palace. The grand hall has witnessed coronations of The Sultans of Kedah as well as a number of highly ranked social events throughout its existence since the year 1735. The architecture of this majestic structure is portraying the traditional Malay style, featuring some influences from Siam and the western world. The arrangements of spaces and ornamentations of Balai Besar signifying the high status of the Sultan, primarily as a host of the social events. The Sultan being well-traveled were said to be inspired by buildings in his journey and decided to build his own mixed style building as part of the royal complex. This study aims to reassess the architectural style of Balai Besar, focusing to explore the traditional Malay architecture of Kedah Tua. The methodology of the research is site visits, observation, and interview. The architectural elements of Balai Besar were analyzed and compared with the local traditional architecture to trace the underlying local and borrowed styles. The styles found is based on two major influence which is British colonial and Siamese. The Malay architectural element would fuse with these foreign styles and create a totally new form of Malay architecture.